Evaluasi UI/UX dan Rancang Bangun Sistem Informasi Penjualan Toko Buku Al-Fithrah Menggunakan UCD - Dori Gusti Alex Candra; Irzon Meiditra; Fauziah Fauziah; Rizky Rahmansyah; Yulia Yulia (Riau Jurnal Teknik Informatika, 2026)
Al-Fithrah Bookstore faces operational challenges in sales due to conventional processes that are still manual. This results in long service times, a high rate of calculation errors, and a high risk of losing report records. This study aims to design a web-based Sales Information System interface using the User-Centered Design (UCD) method. The UCD method was implemented through four iterative stages: understanding the usage context, determining user needs, designing the interface solution, and evaluating the design. This design process resulted in two main interface modules. The customer module is focused on facilitating hybrid search navigation, providing transparency in the shopping cart, and offering up-selling features. Meanwhile, the administrator module is designed to centralize master data management and automatically digitize the printing of daily through annual reports. Usability testing was conducted on 20 respondents using the System Usability Scale (SUS) instrument. The evaluation results showed a significant increase in the usability score, from an initial baseline of 38.5 (the “Awful” category) to a final score of 87.5 (the “Excellent” category). In conclusion, the UCD approach has been empirically proven to reduce users’ cognitive load, minimize interaction errors, and streamline administrative processes, thereby delivering an optimal digital experience